Sarvepalli Radhakrishnan - Singh, Y. K. (New Delhi APH, 2017)
This book titled "Sarvepalli Radhakrishnan" provides readers with an introduction to the life of Dr. Sarvepalli Radhakrishnan. Major works of Dr. Sarvepalli Radhakrishnan are described
Keywords: Presidents; Philosophers